Wiki SaGa: an Interactive Timeline to Visualize Historical Documents - Tan, Daniel Yong Wen; Bali, Ranaivo-Malançon; Narayanan, Kulathuramaiyer (Springer Berlin Heidelberg, 2015)
Searching for information inside a repository of digitised historical documents is a very common task. A timeline interface that represents the historical content which can perform the same search function will reveal better results to researchers. This paper presents the integration of SIMILE Timeline within a wiki, named Wiki SaGa, containing digitised version of Sarawak Gazette. The proposed approach allows display of events and relevant information search compared to traditional list of documents.